The role of Notch and GATA3 in postnatal and adult haematopoiesis - Duarte, S (2011)
The role of Notch in cell fate determination and lineage restriction in the bone marrow (BM) is controversial in the field. Recent studies have convincingly shown that Notch is dispensable for haematopoietic stem cell (HSC) regulation in adult haematopoiesis (Maillard et al., 2008). In contrast, Notch signaling has been proposed to be of importance in the regulation of BM megakaryocyte progenitor differentiation, based on dominant negative genetic approaches, identifying a potentially distinct role for Notch in adult BM haematopoiesis (Mercher et al., 2008). Here, I found that by selectively ablating the gene coding the transcription factor recombination signal-binding protein J kappa (RBP-Jk), to which all canonical Notch signaling converges, canonical Notch signaling does not mediate HSC maintenance, neither in steady state nor in conditions of stress. Furthermore, I propose, in contrast with previous studies (Mercher et al., 2008), that canonical Notch signaling plays no role in myeloerythropoiesis cell lineage commitment in the BM. My data also show that key Notch target genes are suppressed by RBP-Jk, as their expression is unaffected in Notch1-deficient BM progenitors, while target genes are upregulated in Rbp-Jk-deleted megakaryocyte and erythroid progenitors. This establishes for the first time in mammalian cells in vivo, that Notch target genes are kept in a suppressed state by RBP-Jk, potentially restricting T cell commitment to the thymus and not to the BM, at the expense of myeloerythropoiesis. Notch signaling and GATA3 are two master regulators in T cell commitment (Han et al., 2002; Ho et al., 2009; Pui et al., 1999; Radtke et al., 1999; Zhu et al., 2004). However, although very well established as being involved in the thymic stages of T cell restriction, there is little evidence of Notch and GATA3 being involved in the migration of a thymus settling progenitor (TSP) from the BM to the thymus or in the establishment of the earliest thymic progenitor (ETP) in the thymus. From this thesis work, I conclude that Notch signaling is essential for the emergence of ETPs in the thymus in a NOTCH1-independent manner. Moreover, I demonstrate, as supported by a very recent published study (Hosoya et al., 2009), that GATA3 is important for the development of the earliest T cell progenitor. GATA1 and GATA2 mediate haematopoietic stem cell maintenance in the BM. GATA1 is required for erythropoiesis, megakaryocytes and eosinophils while GATA2 is important for the proliferation and survival of HSCs. In contrast, a role for GATA3 in the BM has never been established. By using a Gata3-conditional knockout mouse model, I demonstrate that GATA3 is dispensable for HSC maintenance in steady state and following active haematopoietic regeneration as well as for HSC self-renewal in the BM.